The Common Gut Microbe Eubacterium hallii also Contributes to Intestinal Propionate Formation - Engels, Christina; Ruscheweyh, Hans-Joachim; Beerenwinkel, Niko; Lacroix, Christophe; Schwab, Clarissa (Frontiers in Microbiology, 2016)
Eubacterium hallii is considered an important microbe in regard to intestinal metabolic balance due to its ability to utilize glucose and the fermentation intermediates acetate and lactate, to form butyrate and hydrogen. Recently, we observed that E. hallii is capable of metabolizing glycerol to 3-hydroxypropionaldehyde (3-HPA, reuterin) with reported antimicrobial properties. The key enzyme for glycerol to 3-HPA conversion is the cobalamin-dependent glycerol/diol dehydratase PduCDE which also utilizes 1,2-propanediol (1,2-PD) to form propionate. Therefore our primary goal was to investigate glycerol to 3-HPA metabolism and 1,2-PD utilization by E. hallii along with its ability to produce cobalamin. We also investigated the relative abundance of E. hallii in stool of adults using 16S rRNA and pduCDE based gene screening to determine the contribution of E. hallii to intestinal propionate formation. We found that E. hallii utilizes glycerol to produce up to 9 mM 3-HPA but did not further metabolize 3-HPA to 1,3-propanediol (1,3-PD). Utilization of 1,2-PD in the presence and absence of glucose led to the formation of propanal, propanol and propionate. E. hallii formed cobalamin and was detected in stool of 74% of adults using 16S rRNA gene as marker gene (n = 325). Relative abundance of the E. hallii 16S rRNA gene ranged from 0 to 0.59% with a mean relative abundance of 0.044%. E. hallii PduCDE was detected in 63 to 81% of the metagenomes depending on which subunit was investigated beside other taxons such as Ruminococcus obeum, Ruminococcus gnavus, Flavonifractor prautii, Intestinimonas butyriciproducens, and Veillonella spp. In conclusion, we identified E. hallii as a common gut microbe with the ability to convert glycerol to 3-HPA, a step that requires the production of cobalamin, and to utilize 1,2-PD to form propionate. Our results along with its ability to use a broad range of substrates point at E. hallii as a key species within the intestinal trophic chain with the potential to highly impact the metabolic balance as well as the gut microbiota/host homeostasis by the formation of different short chain fatty acids.